How do infants build a semantic system? - Styles, Suzy J. (2014)
Do infants learn their early words in semantic isolation? Or do they integrate new words into an inter-connected semantic system? In an infant-friendly adaptation of the adult lexical priming paradigm, infants at 18 and 24 months-of-age heard two words in quick succession. The noun-pairs were either related or unrelated. Following the onset of the target word, two pictures were presented, one of which depicted the target. Eye movements revealed that both age groups comprehended the target word. In addition, 24-month-olds demonstrated primed picture looking in two measures of comprehension: Named target pictures preceded by a related word pair took longer to disengage from and attracted more looking overall. The finding of enhanced target recognition demonstrates the emergence of semantic organisation by the end of the second year.